Price competition and endogenous product choice in networks: Evidence from the US airline industry - Christian Bontemps; Cristina Gualdani; Kevin Remmy (Queen Mary University of London, School of Economics and Finance, 2023)
We develop a two-stage game in which competing airlines first choose the networks of markets to serve in the first stage before competing in price in the second stage. Spillovers in entry decisions across markets are allowed, which accrue on the demand, marginal cost, and fixed cost sides. We show that the second-stage parameters are point identified, and we design a tractable procedure to set identify the first-stage parameters and to conduct inference. Further, we estimate the model using data from the domestic US airline market and find significant spillovers in entry. In a counterfactual exercise, we evaluate the 2013 merger between Amer- ican Airlines and US Airways. Our results highlight that spillovers in entry and post-merger network readjustments play an important role in shaping post-merger outcomes.
Keywords: 330; endogenous market structure; multiple equilibria; oligopoly; product repositioning; mergers; remedies; bankruptcy